Warming-induced drought leads to tree growth decline in subtropics: Evidence from tree rings in central China - Jing, Mengdan; Zhu, Liangjun; Liu, Shuguang; Cao, Yang; Zhu, Yu; Yan, Wende (Frontiers in Plant Science, 2022)
Subtropical forests provide diverse ecosystem services to human society. However, how main subtropical tree species respond to climate change is still unclear. Using a dendrochronological method, we studied the radial growth patterns and species-specific responses of four main tree species in subtropical China to recent warming and drought. Results showed that the long-term drought caused by global warming and reduced precipitation since 1997 had resulted in the growth decline of Pinus massoniana, Castanea henryi and Castanopsis eyrie but not for Liquidambar formosana. Tree growth was positively correlated with growing season precipitation and relative humidity while negatively correlated with vapor pressure deficit (VPD). The negative relationship of tree radial growth with temperatures in the previous and current summer and the positive correlation with precipitation gradually strengthened after 1997. Therefore, we highlighted that drought-induced tree decline in subtropical forests is probably a common phenomenon, and it needed to verify by more tree-ring studies on a large scale. The species-specific responses of tree radial growth to climate change should be considered in regional carbon balance and forest dynamics. Taking future climate change into account, species that are more drought tolerant like P. massoniana should be considered as potential plantation species.